Evaluation of microstructure and mechanical properties of PMMA Matrix composites reinforced with residual YSZ from CAD/CAM Milling process : The effect of residue YSZ on PMMA matrix - ÖZDOĞAN, Mahmut; Karslıoğlu, Ramazan (International Journal of Dental Materials, 2021)
Background: Reinforcement of dental acrylics with fillers has yielded positive results. Different proportions of fillers have been added to strengthen the dental acrylics, but no consensus has been reached.Aim: The purpose of this study was to investigate the effects of the addition of different concentrations of yttria-stabilized zirconium (YSZ) obtained from the residues generated from the CAD-CAM milling of YSZ on the microstructure and mechanical properties of poly-methyl-methacrylate (PMMA)-YSZ composites.Materials and methods: Composite materials with different amounts (0.0 to 70.0% by weight) of recycled YSZ reinforced PMMA resin matrix were produced. Scanning electron microscope (SEM), energy dispersive electron spectrometer (EDS) and Fourier Transform Infrared Spectrometer (FTIR) were used for microstructural analysis. Among the mechanical properties, the Vickers microhardness test method for hardness, 2D profilometer for surface roughness and composite densities were evaluated by Archimedes method. Data were analyzed using a one-way analysis of variance (ANOVA) at a pre-set alpha of 0.05.Results: Microhardness and density increased until 60% by weight YSZ addition, while surface roughness remained unchanged but increased after 60% by weight YSZ addition. The addition of more than 60% by weight of YSZ caused agglomeration in the microstructures. The mechanical properties of poly-methyl-methacrylate decreased with more than 60% YSZ by weight.Conclusion: Reinforcement of PMMA with residue zirconia powder will increase the usage chance of residue YSZ powder and provide a safer use of PMMA.